A View of Professional Learning Communities Through Three Frames: Leadership, organization, and culture - Mullen, Carol; Schunk, Dale (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
In this discussion of professional learning communities (PLCs) in North American public schools, we examine three theoretical frames – leadership, organization, and culture. Issues related to learning are infused throughout our presentation of the frames. Based on our analysis of the current literature on this topic, PLCs offer a promising tool for system-wide change and collaborative mentorship in public schools. Implications for collaborative mentorship within PLCs are uncovered in relation to the professional learning of teachers and leaders and their community development. We dovetail the literature on learning, learning communities, and mentoring in order to identify such expanded possibilities for school teams that are supported by practical examples of change.